Porphyrin-based cationic conjugated network prepared by Zincke reaction and its adsorption for TcO4−/ReO4 - Xu, Yuwei; Tian, Yin; Chen, Bo; Yan, Zijun; Ding, Jie; Huang, Yalin; Kang, Jinyang; Chen, Shanyong; Jin, Yongdong; Xia, Chuanqin (Journal of radioanalytical and nuclear chemistry, 2021)
In this paper, porphyrin-based cationic conjugated network (PCCN) nanosheets were synthesized, and its adsorption for TcO 4 − /ReO 4 − was investigated. This material was stacked with AB dislocation, with an aperture of 1.2 nm. The Re(VII)/Tc(VII) adsorption kinetics of PCCN is extremely fast, and the adsorption capacity is relatively large, the selective order is ReO 4 − > NO 3 − > Cl − . XPS and DFT revealed that the exchange of Cl − on PCCN with ReO 4 − , while the hydrophobic pore of PCCN are the keys to improve adsorption selectivity. It could be used to remove Tc from groundwater around nuclear facilities. Graphic abstract